Distribusi Barium Terlarut pada Estuari dan Laut Padelegan Kecamatan Pademawu, Kabupaten Pamekasan - Hidayatullah, Muhamad Aziz; Pratiwi, Wiwit Sri Werdi; Kartika, Ary Giri Dwi; Indriyawati, Novi; Efendi, Makhfud (Buletin Oseanografi Marina, 2024)
Barium (Ba) merupakan salah satu elemen minor di perairan laut yang memiliki nilai ekonomis tinggi apabila dimanfaatkan sebagai produk garam turunan. Sumber utama Ba terlarut berasal dari sungai, dan estuari menjalankan peran penting sebagai pengontrol fluktuasi kadar Ba terlarut pada sungai sebelum masuk ke laut. Penelitian ini bertujuan untuk mengetahui kadar Ba terlarut, distribusi Ba terlarut dan korelasi Ba terlarut dengan salinitas. Kadar Ba terlarut diketahui dari hasil pengujian sampel air laut yang diambil di 9 titik mulai dari daerah estuari hingga laut lepas. Pengujian kadar Ba terlarut menggunakan metode Atomic Absorption Spectrophotometry sesuai SNI 06-6989.39-2005. Kadar Ba terlarut di Perairan Padelegan berkisar antara 0,009-0,003 mg/L. Hasil visualisasi distribusi kadar Ba terlarut tertinggi berada di estuari dan kadar terendahnya berada di stasiun laut lepas. Distribusi Ba terlarut dari estuari hingga laut lepas menunjukkan kadar yang menurun secara bertahap. Hasil korelasi antara kadar barium terlarut dengan salinitas berbanding lurus yang disebabkan oleh intrusi air laut.  Barium (Ba) is a minor element in marine waters which has high economic value when used as a derivative salt product. The main source of dissolved Ba comes from rivers, and estuaries play an important role as controlling fluctuations in dissolved Ba levels in rivers before they enter the sea. This research aims to determine dissolved Ba levels, dissolved Ba distribution and the correlation of dissolved Ba with salinity. Dissolved Ba levels are known from the results of testing seawater samples taken at 9 points from the estuary area to the open sea. Dissolved Ba levels were tested using Atomic Absorption Spectrophotometry based on SNI SNI 06-6989.39-2005. Dissolved Ba levels in Padelegan Water range between 0,009-0,003 mg/L. Visualization results of the distribution of the highest dissolved Ba levels are in estuaries and the lowest levels are at open sea. The distribution of dissolved Ba from the estuary to the open sea shows gradually decreasing levels. Correlation results between dissolved barium levels and directly proportional salinity caused by seawater intrusion.